Iron management in chronic kidney disease: Conclusions from a "kidney Disease: Improving Global Outcomes" (KDIGO) Controversies Conference - Macdougall, Iain C. (2016)
Before the introduction of erythropoiesis-stimulating agents (ESAs) in 1989, repeated transfusions given to patients with end-stage renal disease caused iron overload, and the need for supplemental iron was rare. However, with the widespread introduction of ESAs, it was recognized that supplemental iron was necessary to optimize hemoglobin response and allow reduction of the ESA dose for economic reasons and recent concerns about ESA safety. Iron supplementation was also found to be more efficacious via intravenous compared to oral administration, and the use of intravenous iron has escalated in recent years. The safety of various iron compounds has been of theoretical concern due to their potential to induce iron overload, oxidative stress, hypersensitivity reactions, and a permissive environment for infectious processes. Therefore, an expert group was convened to assess the benefits and risks of parenteral iron, and to provide strategies for its optimal use while mitigating the risk for acute reactions and other adverse effects.